Markov multi-variate survival indicators for default simulation as a new characterization of the Marshall-Olkin law - Brigo,D; Mai,JF; Scherer,M (Statistics & Probability Letters, 2016)
A new characterization of the Marshall–Olkin distribution is provided: all subvectorsof the associated survival indicators are continuous-time Markov chains.This property is crucial to overcome practical limitations for the modeling of highdimensionaldefault times (rebalancing, iterative simulation, consistent sub-portfolios).